DAYA TARIK WISATA ROHANI SALIB KASIH TARUTUNG SEBAGAI PUSAT DESTINASI WISATA BERSPIRITUALITAS KRISTEN DI TAPANULI UTARA - Vega, Lydia De (Akademi Pariwisata Darma Agung, 2024)
This research is entitled The Spiritual Tourism Attraction of Tarutung'sSalib Kasih as a Center for Christian Spiritual Tourism Destinations in North Tapanuli. Salib Kasih Tarutung is one of the famous spiritual tourist destinations in North Tapanuli, North Sumatra, which has its main attraction as a center of Christian spirituality. This monument was built to commemorate the German missionary, Dr. Ingwer Ludwig Nommensen, who played an important role in the spread of Christianity in the region. Apart from being a place of worship, the Salib Kasih also offers a beautiful natural panorama from the peak of DolokSiatas Barita, as well as a strong religious atmosphere, making it a favorite place for spiritual pilgrimage, meditation and contemplation. Research using qualitative methods with a descriptive approach to data collection techniques, namely observation, interviews and documentation studies. This research aims to identify the factors that make Lintas Kasih an attractive spiritual tourism destination and its relevance in supporting the development of spirituality-based tourism in North Tapanuli.